2011
DOI: 10.1074/jbc.m110.196097
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Immunogenicity of Arabidopsis hgl1 Mutant N-Glycans Caused by Altered Accessibility of Xylose and core Fucose Epitopes

Abstract: Arabidopsis N-glycosylation mutants with enhanced salt sensitivity show reduced immunoreactivity of complex N-glycans. Among them, hybrid glycosylation 1 (hgl1) alleles lacking Golgi ␣-mannosidase II are unique, because their glycoprotein N-glycans are hardly labeled by anti-complex glycan antibodies, even though they carry ␤1,2-xylose and ␣1,3-fucose epitopes. To dissect the contribution of xylose and core fucose residues to plant stress responses and immunogenic potential, we prepared Arabidopsis hgl1 xylT d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
43
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(49 citation statements)
references
References 51 publications
(59 reference statements)
6
43
0
Order By: Relevance
“…Stronger effects caused by cgl1 or hgl1 could be attributed to persisting mannoses on the a1,6-branch, but in the case of hgl1, also alter the availability/ accessibility of core fucoses. We previously demonstrated that the a1,3-fucose epitope present in hgl1 mutants was recognized by complex glycan-and fucose-specific antibodies only after enzymatic digestion of the bulky mannoses on the a1,6-arm (Kaulfürst-Soboll et al, 2011). These immunologic and modeling results support our hypothesis that complex N-glycans could function as an important interface between glycoproteins and their interacting partners.…”
Section: Discussionsupporting
confidence: 73%
See 2 more Smart Citations
“…Stronger effects caused by cgl1 or hgl1 could be attributed to persisting mannoses on the a1,6-branch, but in the case of hgl1, also alter the availability/ accessibility of core fucoses. We previously demonstrated that the a1,3-fucose epitope present in hgl1 mutants was recognized by complex glycan-and fucose-specific antibodies only after enzymatic digestion of the bulky mannoses on the a1,6-arm (Kaulfürst-Soboll et al, 2011). These immunologic and modeling results support our hypothesis that complex N-glycans could function as an important interface between glycoproteins and their interacting partners.…”
Section: Discussionsupporting
confidence: 73%
“…These results reveal that core a1,3-fucose attachment is an important host N-glycan modification for in vivo functionality of KOR1. However, this is not more important than mannose trimming ( Figure 9B) because persisting mannoses on the a1,6-branch produce more severely impaired phenotypes in rsw2-1 hgl1-1 whose N-glycans still receive core a1,3-fucose (Strasser et al, 2006;Kaulfürst-Soboll et al, 2011). Neither hgl1-1 nor fucTa/b double mutants without rsw2-1 showed growth defects in the absence of osmotic stress (Kang et al, 2008).…”
Section: Complex N-glycans May Promote Kor1 Function In Transmentioning
confidence: 99%
See 1 more Smart Citation
“…Problems with degradation and plant-specific PTMs were identified, highlighting the need for additional engineering for plants to become versatile production platforms of therapeutics. Although in its infancy, engineering O-glycosylation capacities in plants may eventually be combined with engineered human N-glycosylation (Strasser et al, 2008;Kaulfürst-Soboll et al, 2011;Nagels et al, 2011;Schoberer and Strasser, 2011) to generate more general platforms for the expression of glycoprotein pharmaceuticals in plants.…”
Section: Discussionmentioning
confidence: 99%
“…However, stoichiometry and subcellular localization of the introduced glycoenzymes and subcellular substrate pools are increasingly difficult to control as the engineering effort increases in complexity. Stable engineering of especially the glycosylation machineries is thus generally needed at an early point, as seen in the engineering efforts to humanize plants with respect to N-linked protein glycosylation (Strasser et al, 2008;Castilho et al, 2010;Kaulfürst-Soboll et al, 2011;Nagels et al, 2011;Schoberer and Strasser, 2011;Yin et al, 2011).…”
mentioning
confidence: 99%